Method for manufacturing electric motor core
By using the fuse processing of heat input from the surface on the electromagnetic steel plate of the motor core, the thermal conductivity ratio is reduced to suppress strain and heat influence, the problems of deterioration of magnetic characteristics and processing difficulty of miniaturized motor core are solved, and high-efficiency and low-cost motor core manufacturing is achieved.
Patent Information
- Application Number
- CN202080037298.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-05-28
- Filing Date
- 2020-05-15
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2040-05-15
AI Technical Summary
In a miniaturized and high-speed rotating motor, the excitation frequency of the motor core becomes higher, resulting in deterioration of magnetic characteristics, increasing difficulty in punching and processing, reducing yield, and increasing cost.
By processing the electromagnetic steel plate by fuse from the heat input from the surface, the average thermal conductivity from the surface to the depth position of 1/3 of the plate thickness is more than 30% lower than the thermal conductivity in the center position in the plate thickness direction, and the thermal influence and strain introduction during laser processing are suppressed.
It effectively suppresses the deterioration of the magnetic properties of the electromagnetic steel plate, improves the processing yield and motor efficiency of the motor core, and reduces costs.
Smart Images

Figure CN113853732B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for manufacturing a motor core. Background Art
[0002] In recent years, the demand for miniaturization of electric motors has become increasingly strong, represented by electric motors used in the aerospace field and cordless vacuum cleaners. For such small motors, in order to maintain output while seeking miniaturization, high-speed rotation is constantly developing. With the high-speed rotation of the motor, the excitation frequency of the motor core becomes higher. In addition, in order to compensate for the motor torque reduced by the miniaturization of the motor, the number of poles of the rotor magnet is increased, and the excitation frequency of the motor core is getting higher and higher. As the core material of such a high-speed motor, low iron loss characteristics at high frequencies are required, and a large amount of alloy elements such as Si and Al that increase the resistivity and a reduction in plate thickness are used as effective means. However, the large amount of alloy elements and thinning will make the punching process of the motor core difficult. In particular, when seeking miniaturization, the motor core becomes very small, so the poor punching processability of the electromagnetic steel sheet used as the core material has problems such as reduced punching yield and increased costs. Therefore, various studies have been made on a motor core processing method that uses a laser or the like to fuse an electromagnetic steel sheet instead of punching (see Non-Patent Document 1).
[0003] Prior art literature
[0004] Non-patent literature
[0005] Non-patent document 1: "Effect of laser cutting on microstructure and onmagnetic properties of grain non-oriented electrical steels", Journal of Magnetism and Magnetic Materials 256 (2003) 20-31 Summary of the invention
[0006] Problems to be solved by the invention
[0007] However, it is known that in the motor core processing method using laser or the like, the magnetic properties of the electromagnetic steel sheet are deteriorated due to the strain introduced into the electromagnetic steel sheet accompanying the heat input and cooling into the electromagnetic steel sheet. The deterioration of the magnetic properties of the electromagnetic steel sheet caused by the strain introduced by laser or the like is greater than that in the case of punching processing, so the motor core processing method using laser or the like has problems as a method for manufacturing the motor core.
[0008] The present invention has been made in view of the above-mentioned problems, and an object of the present invention is to provide a method for manufacturing a motor core suitable for a small-sized and high-speed rotating motor.
[0009] Methods used to solve problems
[0010] The method for manufacturing a motor core of the present invention comprises the steps of manufacturing a motor core by processing an electromagnetic steel sheet whose average thermal conductivity from the surface to a depth position of 1 / 3 of the sheet thickness is at least 30% lower than the thermal conductivity at the center position in the sheet thickness direction, by utilizing melting due to heat input from the surface.
[0011] The electromagnetic steel sheet preferably has a thickness of 0.20 mm or less.
[0012] The concentrations of Si, Al, and Mn in the electromagnetic steel sheet from the surface to a depth of 1 / 3 of the sheet thickness preferably satisfy the condition represented by the following mathematical formula (1).
[0013] Al+Si≥10Mn…(1)
[0014] The component concentrations of the electromagnetic steel sheet in the entire sheet thickness are preferably, in mass %, C: 0.01% or less, Si: 7% or less, Al: 4% or less, and Mn: 5% or less.
[0015] Effects of the Invention
[0016] According to the present invention, it is possible to provide a method for manufacturing a motor core suitable for a small-sized and high-speed rotating motor. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 It is a plan view showing the structure of the motor core according to the embodiment.
[0018] Figure 2 This is a graph showing the relationship between the thermal conductivity ratio of a motor core manufactured by laser processing and punching processing and the motor efficiency.
[0019] Figure 3 This is a diagram showing an example of the relationship between the depth in the plate thickness direction and the thermal conductivity. DETAILED DESCRIPTION
[0020] The inventors of the present invention investigated the degradation of the magnetic properties of electromagnetic steel sheets caused by laser processing and its mechanism, and conducted in-depth research and development on electromagnetic steel sheets that suppress this degradation. Here, the degradation of the magnetic properties of the electromagnetic steel sheets caused by laser processing is caused by the strain widely introduced from the surface of the electromagnetic steel sheet along the plane direction of the electromagnetic steel sheet due to the heat input and cooling introduced by the laser. On the other hand, in order to melt the electromagnetic steel sheet before the strain spreads in the plane direction, it is preferred that the heat input from the surface is actively transmitted to the inside of the electromagnetic steel sheet, and is not easily transmitted in the plane direction. Based on the above insights and ideas, the inventors of the present invention conducted the experiments shown below and conceived the present invention.
[0021] First, in order to clarify the effects of laser processing conditions and the thermal conductivity inside the electromagnetic steel sheet on the motor efficiency, the motor was trial-produced and evaluated using 0.10 mm thick electromagnetic steel sheets with the same iron loss at 1.0T-1000Hz but different thermal conductivity in the thickness direction. These electromagnetic steel sheets were made by using cold-rolled steel sheets with Si concentrations equivalent to the center layer shown in Table 1 below and increasing the Si concentration of the surface layer by siliconizing. It should be noted that the motor core was processed by punching or laser processing.
[0022] As a result, it was found that, in an electromagnetic steel sheet whose average thermal conductivity from the surface to a depth position of 1 / 3 of the plate thickness (represented as surface average thermal conductivity in Table 1) is 30% or more lower than the thermal conductivity at the center position in the plate thickness direction, the deterioration of the magnetic properties of the electromagnetic steel sheet due to laser processing is small. In addition, it was found that, as a preferred structure of the electromagnetic steel sheet, when the concentrations of Si, Al, and Mn from the surface to a depth position of 1 / 3 of the plate thickness satisfy the mathematical formula (1) shown below, an electromagnetic steel sheet with excellent magnetic properties and less deterioration of magnetic properties can be obtained, and the invention was conceived.
[0023] Al+Si≥10Mn…(1)
[0024] It is known that Si, Al, and Mn improve the magnetic properties of electromagnetic steel sheets by increasing the resistivity of the electromagnetic steel sheets and reducing eddy current losses. However, Mn increases the thermal expansion coefficient of the electromagnetic steel sheets, so when heat is input from the surface, the heat-affected zone expands, promoting the introduction of strain into the electromagnetic steel sheets. Therefore, it is believed that Mn can further suppress the deterioration of the magnetic properties of the electromagnetic steel sheets by adding an appropriate amount relative to the addition amount of Si and Al. It should be noted that the present invention was conceived through research efforts based on laser processing, but the same effect can be obtained by using a fusing process using heat input from the surface, such as a fusing process using an electron beam.
[0025] Hereinafter, a method for manufacturing a motor core according to the present invention will be described.
[0026] In the method for manufacturing the motor core of the present invention, an electromagnetic steel sheet whose average thermal conductivity from the surface to a depth of 1 / 3 of the sheet thickness is 30% or more lower than the thermal conductivity at the center position in the sheet thickness direction is processed by melting using heat input from the surface, thereby suppressing the thermal influence on the plane direction of the electromagnetic steel sheet during laser processing, and facilitating the melting of the electromagnetic steel sheet by allowing heat to pass in the sheet thickness direction. As a result, it is possible to suppress the introduction of strain into the electromagnetic steel sheet, thereby suppressing the degradation of the magnetic properties of the electromagnetic steel sheet.
[0027] Here, the electromagnetic steel sheets that were cold rolled to the final product thickness were subjected to a heat treatment at 1200°C in SiCl4, and the amount of Si in the surface layer was adjusted in various ways to change the average thermal conductivity from the surface to a depth of 1 / 3 of the sheet thickness and the thermal conductivity at the center of the sheet thickness. Figure 1 The efficiency of the motor was evaluated using the small motor (tooth width 8.0 mm) shown in the figure. The motor core was processed by laser processing or punching. In the case of laser processing, a CO2 pulse laser with a frequency of 1500 Hz and an output of 500 W was used, and oxygen was blown at 5 MPa as an auxiliary gas, and the scanning speed of the laser was set to about 5000 mm / min. In addition, the driving conditions of the motor were set to 50 mNm-90000 rpm, and the output was measured using the motor torque tester EMM-100M manufactured by Sugawara Laboratory.
[0028] The obtained results are shown in the following Table 1, and the relationship between the ratio of the average thermal conductivity from the surface to the position at a depth of 1 / 3 of the plate thickness to the thermal conductivity at the center position in the plate thickness direction (thermal conductivity ratio) and the motor efficiency is shown in Table 1. Figure 2 . It can be seen from this that the influence of the thermal conductivity ratio on the motor efficiency is not found in the motor core manufactured by punching, but in the motor core manufactured by laser processing, the motor efficiency is significantly improved when the thermal conductivity ratio is 0.7 or less (that is, the average thermal conductivity from the surface to the depth position of 1 / 3 of the plate thickness is 30% or more lower than the thermal conductivity at the center position in the plate thickness direction). It is further preferred that the average thermal conductivity from the surface to the depth position of 1 / 3 of the plate thickness is 50% or more lower than the thermal conductivity at the center position in the plate thickness direction.
[0029]
[0030] The method of imparting a change in the thermal conductivity in the thickness direction to the electromagnetic steel sheet is not particularly limited, and for example, as shown in the examples described later, a siliconizing technology of subjecting the electromagnetic steel sheet to a chemical vapor deposition (CVD) treatment, a manufacturing technology of a composite steel formed by joining electromagnetic steel sheets with different components, etc. can be used. Here, the thermal conductivity in the thickness direction can be evaluated using a thermophysical property microscope (manufactured by Betel: SAMAR Microscope TM3) or the like. It should be noted that the absolute value of the thermal conductivity of the electromagnetic steel sheet has nothing to do with the effect of the invention, but in order to perform processing by heat input using a laser, the average thermal conductivity of the total thickness is preferably 10 W / mK or more, and more preferably 15 W / mK or more.
[0031] It should be noted that for high-speed rotating electric motors, since low iron loss characteristics at high frequencies are required, the thickness of the electromagnetic steel sheet is preferably set to be 0.20 mm or less, which is an effective thickness for reducing eddy currents, more preferably 0.15 mm or less, and even more preferably 0.10 mm or less.
[0032] In order to reduce the iron loss at high frequencies, it is effective to add an element that increases the resistivity of the electromagnetic steel sheet. However, when Mn is added in excess, the strain introduced into the electromagnetic steel sheet during laser processing is accelerated due to the increase in the thermal expansion coefficient, so the magnetic properties of the electromagnetic steel sheet may be deteriorated. Therefore, it is preferred that the concentrations of Si, Al, and Mn from the surface to a depth of 1 / 3 of the sheet thickness satisfy the relationship shown in the following mathematical formula (1), and the amount of Mn added is less than a certain amount relative to the amount of Al and Si added.
[0033] Al+Si≥10Mn…(1)
[0034] In addition, when there is an excessive amount of C (carbon) in the electromagnetic steel sheet, magnetic aging occurs, which deteriorates the magnetic properties of the electromagnetic steel sheet. Therefore, the carbon concentration of the entire thickness of the electromagnetic steel sheet is 0.01% or less, preferably 0.001% or less, in terms of mass%. In addition, Si, Al, and Mn increase the resistivity of the electromagnetic steel sheet and contribute to the reduction of eddy current loss, so their addition is effective, but on the other hand, excessive addition of these elements leads to the saturation magnetic flux density of the electromagnetic steel sheet. Therefore, the concentration (average concentration) of the entire thickness of the electromagnetic steel sheet is preferably set to Si: 7% or less, Al: 4% or less, and Mn: 5% or less, respectively, in terms of mass%.
[0035] Furthermore, since the deterioration of the magnetic properties of the electromagnetic steel sheet due to the influence of strain introduced during processing becomes significant when the tooth width is 10 mm or less, the method for manufacturing the motor core of the present invention is preferably targeted at motors having a tooth width of 10 mm or less.
[0036] In addition, the electromagnetic steel sheet of the present invention is an electromagnetic steel sheet with less deterioration of magnetic properties caused by strain introduction caused by heat input from the surface. Therefore, by processing using heat input of laser, electron beam, etc., it is possible to manufacture a motor core with excellent magnetic properties compared with processing using shearing. There is no restriction on the conditions of laser processing (such as output, gas conditions) and electron beam processing conditions (such as acceleration voltage or current, atmosphere during irradiation), and they can be adjusted according to the plate thickness of the core material, the required processing speed, etc. However, in the present invention, since an electromagnetic steel sheet thinner than 0.20 mm in thickness is used as the object of processing, the use of an unnecessary high-output laser will promote the introduction of strain caused by heat, which is not preferred from the perspective of magnetic properties. Therefore, the laser output is preferably 500 W or less, and more preferably 250 W or less. In addition, from the same point of view, it is preferred that the laser diameter is small, and it is preferred to use a single-mode fiber laser with a diameter of 50 μm or less.
[0037] In addition, the necessity of the insulating film for the electromagnetic steel sheet used is the same as that of the ordinary electromagnetic steel sheet, and the electromagnetic steel sheet may be provided with an insulating film having sufficient insulation properties on one or both sides in advance. In addition, in the present invention, it is assumed that the use of strain relief annealing after the core is formed, which increases not only the manufacturing cost but also the equipment investment cost, is not implemented. It should be noted that when forming the core, the stacking of the electromagnetic steel sheets can be fixed by riveting, bonding, etc., and there is no particular limitation on the method.
[0038] In addition, it is effective to add the following elements to the electromagnetic steel sheet used within a range to improve the magnetic properties. For Sn, P, and Sb, it is preferred to add 0.001% or more within a range of 0.1% or less as needed. This is because the magnetic flux density of the core is improved by improving the texture. On the other hand, when the addition amount is greater than 0.1%, the effect is saturated, resulting in an unnecessary increase in cost, so the upper limit of the addition amount is set to 0.1%.
[0039] The method for producing the electromagnetic steel sheet used is not particularly limited as long as it can form an electromagnetic steel sheet that satisfies the above conditions, and various methods can be applied. For example, the following production methods (1) to (3) can be exemplified.
[0040] (1) Materials with different compositions are blown in a converter, and the molten steel is degassed to adjust the composition to a predetermined value, and then cast to form a slab, which is then surface-finished and bonded, and then welded using an electron beam or the like. The slab is then hot-rolled using a conventional method, and then cold-rolled or warm-rolled once, or cold-rolled or warm-rolled twice or more with intermediate annealing, to a predetermined thickness, and then finally annealed.
[0041] (2) A material of a specified composition is blown in a converter, the molten steel is degassed and adjusted to a specified composition, the slab is hot rolled by a conventional method, and then the slab is made into a specified plate thickness by a single cold rolling or warm rolling, or by two or more cold rolling or warm rolling with intermediate annealing. Then, elements such as Si are infiltrated into the surface of the electromagnetic steel sheet by a CVD method or the like, thereby forming a thermal conductivity distribution in the thickness direction of the plate.
[0042] (3) The material of the specified composition is blown in a converter, the molten steel is degassed and adjusted to the specified composition, the slab is hot rolled by a conventional method, and then the slab is made into a specified plate thickness by a single cold rolling or warm rolling, or by two or more cold rolling or warm rolling with intermediate annealing. Then, aluminum foil is attached to the electromagnetic steel plate, and final annealing is performed in a non-oxidizing atmosphere.
[0043] [Example 1]
[0044] Electromagnetic steel sheets used as raw materials for motor cores were produced by the composition in the plate thickness direction and the production method shown in Table 2 below. These electromagnetic steel sheets were evaluated for thermal conductivity in the plate thickness direction and iron loss (W) based on the Epstein test specified in JIS C2550-1. 10 / 1000 ). As an example, in Figure 3 The results of measuring the thermal conductivity of No. 1 electromagnetic steel sheet in the thickness direction are shown in FIG. Figure 1 The small motor shown in the figure was used to evaluate the motor efficiency. Here, the driving condition of the motor was set to 50mNm-90000rpm, and the output was measured using the motor torque tester EMM-100M manufactured by Sugawara Laboratory. It should be noted that the symbols of the manufacturing methods of the electromagnetic steel sheets in Table 2 correspond to the above-mentioned manufacturing methods (1) to (3). The conditions of each intermediate process are as follows, and the conditions are adjusted in such a way that the layers with different compositions are each 1 / 3 in the surface layer (surface and back) and the center layer.
[0045] (1) Blowing is performed in a converter, followed by degassing to adjust the composition to a specified value, followed by casting, surface finishing, and bonding of slabs of different compositions. The slabs are then reheated to 1200°C and hot rolled to a thickness of 1.8 mm. Furthermore, they are cold rolled to the final product thickness and annealed at 1000°C in a dry N2 atmosphere.
[0046] (2) After blowing in a converter, the steel is degassed to adjust the composition to a predetermined value, and then cast. The slab is then reheated to 1200°C and hot rolled to a thickness of 1.8 mm. Furthermore, the steel is cold rolled to the final product thickness, and heat treated at 1200°C in SiCl4 to adjust the Si content in the surface layer.
[0047] (3) After blowing in a converter, the steel sheet is degassed to adjust the composition to a predetermined value, and then cast. After surface finishing, the slab is reheated to 1200°C and hot rolled to a thickness of 1.8 mm. Furthermore, the slab is cold rolled to the final product thickness, and 10 μm aluminum foil is attached to both sides of the electromagnetic steel sheet. The electromagnetic steel sheets are stacked and restrained, and then annealed at 900°C for 5 hours in a N2 atmosphere.
[0048] It should be noted that the motor core is processed by laser processing or punching. In the case of laser processing, a CO2 pulse laser with a frequency of 1500 Hz and an output of 500 W is used, oxygen is blown as an auxiliary gas at 5 MPa, and the laser scanning speed is set to about 5000 mm / min.
[0049] The evaluation results are shown in Table 2 shown below. As shown in Table 2, it can be seen that for materials in which the thermal conductivity of the surface layer of the electromagnetic steel sheet is 30% or more lower than that of the center, high-efficiency motor characteristics can be obtained. On the other hand, for materials in which the thermal conductivity of the surface layer is not 30% or more lower than that of the center, although the Epstein iron loss value is excellent, the motor efficiency is poor. In addition, when No. 1 and No. 2 are compared, although the electromagnetic steel sheet is made of the same material, the motor efficiency of No. 2 in which the iron core is processed by punching is poor. It is believed that this is because the magnetic properties of the electromagnetic steel sheet of the present invention deteriorate less during laser processing than during punching. In addition, under the condition that the composition of the surface layer satisfies the above-mentioned mathematical formula (1), the efficiency of the motor formed by laser processing tends to increase. It is believed that this is because the increase in the thermal expansion coefficient caused by the presence of Mn in the surface layer is suppressed, and the strain introduced into the electromagnetic steel sheet during heat input is further reduced.
[0050]
[0051] [Example 2]
[0052] The influence of the laser conditions used in the processing of material No. 5 shown in Table 2 was evaluated. The evaluation method other than the laser conditions was the same as that in Example 1. The results of the motor evaluation are shown together with the laser conditions in the following Table 3. As shown in Table 3, under the condition of irradiation with a CO2 laser in a continuous oscillation mode, the motor efficiency is poor compared to the condition of processing with a CO2 laser in a pulse oscillation mode with the same output. On the other hand, under the condition of processing with a CO2 laser in a pulse oscillation mode and a low output of 250W, the motor efficiency is excellent. In addition, by using a fiber laser as an oscillation source instead of a CO2 laser, the improvement in motor efficiency is further confirmed.
[0053] [Table 3]
[0054] (Table 3)
[0055]
[0056] Industrial Applicability
[0057] According to the present invention, it is possible to provide a method for manufacturing a motor core suitable for a small-sized and high-speed rotating motor.
Claims
1. A method for manufacturing a motor core, comprising the following steps: The motor core is manufactured by processing an electromagnetic steel sheet whose average thermal conductivity from the surface to a depth of 1 / 3 of the sheet thickness is 30% or more lower than the thermal conductivity at the center position in the sheet thickness direction by melting using heat input from the surface, The Si, Al, and Mn concentrations of the electromagnetic steel sheet from the surface to a depth of 1 / 3 of the sheet thickness satisfy the condition represented by the following mathematical formula (1): Al+Si≥10Mn…(1).
2. The method for manufacturing a motor core according to claim 1, wherein: The electromagnetic steel sheet has a thickness of 0.20 mm or less.
3. The method for manufacturing a motor core according to claim 1 or 2, wherein: The component concentrations of the electromagnetic steel sheet throughout the entire thickness of the sheet are, by mass%, C: 0.01% or less, Si: 7% or less, Al: 4% or less, and Mn: 5% or less.
Citation Information
Patent Citations
Manufacturing method for electromagnetic steel laminated core
JP2009032753A
Unidirectional electromagnetic steel plate and manufacturing method thereof
JP2009164542A
Grain-oriented magnetic steel sheet and manufacturing method therefor
JP2009263782A
Laminate iron core, stress relieving annealing method and manufacturing method therefor
JP2017186586A